Feature Papers "Age-Friendly Cities & Communities: State of the Art and Future Perspectives" (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The "Age-Friendly Cities & Communities: States of the Art and Future Perspectives" publication presents contemporary, innovative, and insightful narratives, debates, and frameworks based on an international collection of papers from scholars spanning the fields of gerontology, social sciences, architecture, computer science, and gerontechnology. This extensive collection of papers aims to move the narrative and debates forward in this interdisciplinary field of age-friendly cities and communities.